Chemokines in Alzheimer's Disease: New Insights Into Prokineticins, Chemokine-Like Proteins - Anna Rita Zuena; Paola Casolini; Roberta Lattanzi; Daniela Maftei (Frontiers Media S.A., 2019)
Alzheimer's disease is the most common neurodegenerative disorder characterized by the presence of β-amyloid aggregates deposited as senile plaques and by the presence of neurofibrillary tangles of tau protein. To date, there is a broad consensus on the idea that neuroinflammation is one of the most important component in Alzheimer's disease pathogenesis. Chemokines and their receptors, beside the well-known role in the immune system, are widely expressed in the nervous system, where they play a significant role in the neuroinflammatory processes. Prokineticins are a new family of chemokine-like molecules involved in numerous physiological and pathological processes including immunity, pain, inflammation, and neuroinflammation. Prokineticin 2 (PROK2) and its receptors PKR1 and PKR2 are widely expressed in the central nervous system in both neuronal and glial cells. In Alzheimer's disease, PROK2 sustains the neuroinflammatory condition and contributes to neurotoxicity, since its expression is strongly upregulated by amyloid-β peptide and reversed by the PKR antagonist PC1. This review aims to summarize the current knowledge on the neurotoxic and/or neuroprotective function of chemokines in Alzheimer's disease, focusing on the prokineticin system: it represents a new field of investigation that can stimulate the research of innovative pharmacotherapeutic strategies.